2001
DOI: 10.2202/0027-6014.1142
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Self-Assessment and Peer Assessment of Leadership Skills

Abstract: Members of a residential leadership community reported whether they had practiced specific leadership skills in the preceding semester and, if so, how well they believed they had performed on that skill. Results were compared with the responses of peer observers. Self-reports of leadership practices were confirmed by peer reports in 72% of cases. Self-assessments of the quality of performance were confirmed by peer assessments in 83% of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Cross-sectional designs with retrospective questions provide a stronger indication of student gains by reducing concerns associated with response-shift bias when measuring self-reported leadership outcomes (Howard, 1980;Rohs, 2002;Rohs & Langone, 1997). Furthermore, a study of self-and peer-reported leadership behaviors and the quality of those behaviors found self-reports of leadership to be generally accurate (Turrentine, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Cross-sectional designs with retrospective questions provide a stronger indication of student gains by reducing concerns associated with response-shift bias when measuring self-reported leadership outcomes (Howard, 1980;Rohs, 2002;Rohs & Langone, 1997). Furthermore, a study of self-and peer-reported leadership behaviors and the quality of those behaviors found self-reports of leadership to be generally accurate (Turrentine, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…This study addressed these considerations through rigorous pilot testing focused on establishing the validity and reliability of measures as well as on the ease of interpretation and recall (see Dugan et al, 2009). Concerns related to self-report data are further reduced given the focus of the study on leadership, a content area for which previous research has established general accuracy between self-reported and peer-reported behaviors (e.g., Turrentine, 2001).…”
Section: Limitationsmentioning
confidence: 99%
“…Through pilot tests and on-going psychometric research on the SRLS, MSL researchers have explored these concepts and continued to evolve the rigor of the SRLS when used in selfreport and cross-sectional designs. This is further bolstered by studies specifically on the topic of leadership, which found self-reports to be generally accurate (Turrentine, 2001;Posner, 2012). For example, Posner (2012) used a large, international sample to examine self-report versus peer observations across five leadership behaviors (i.e., inspiring a shared vision, enabling…”
Section: Considerations Of Cross-sectional and Self-report Designsmentioning
confidence: 99%